MASS MEDIA: ANALYSIS OF COMMUNICATION PATTERNS BETWEEN PARENTS AND CHILDREN - Husin Husin; Hj. Salamah; Abdul Rashid bin Abdul Aziz (International Forum of Researchers and Lecturers, 2022)
Social media creates change in the world. Social media is the most crucial medium used in obtaining information. Various types of social media have been attached to community activities, one of which is Instagram. On the Instagram account @Parentaltalk.id where a video of a child aged about 12 begging his father to give him a break, telling his father that he needs